2003
DOI: 10.1136/thorax.58.10.908
|View full text |Cite
|
Sign up to set email alerts
|

Primary pleural lymphomas

Abstract: Two patients are presented with primary low grade pleural B cell lymphomas with no history of a pyothorax.P leural disease in non-Hodgkin's lymphoma is well documented and commonly presents with pleural effusions in 20% of patients. 1 However, solid pleural involvement is less common and is usually a secondary event. Primary pleural lymphomas are extremely rare and, in a series reported by Burgener and Hamlin, pleural plaques were seen in less then 4% of cases. 2 Two types of primary pleural lymphomas have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 3 publications
0
32
0
Order By: Relevance
“…Also, he had an extranodal follicular NHL, which has not been reported so far. In adult patients without chronic pyothorax, Ahmad et al [5] reported 2 cases of low-grade marginal zone lymphoma and Kano et al [6] reported cases of diffuse large B cell lymphoma. Only one case in a pediatric patient, a 2.5-year-old girl with lymphoblastic lymphoma, has been reported by Karadeniz et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…Also, he had an extranodal follicular NHL, which has not been reported so far. In adult patients without chronic pyothorax, Ahmad et al [5] reported 2 cases of low-grade marginal zone lymphoma and Kano et al [6] reported cases of diffuse large B cell lymphoma. Only one case in a pediatric patient, a 2.5-year-old girl with lymphoblastic lymphoma, has been reported by Karadeniz et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…Both are clinically aggressive and have well-characterised clinical and pathological features. Various mechanisms have been implicated for the development of primary pleural lymphoma, including chronic stimulation of B cells by longstanding chronic pleural disease, which occurs in different diseases such as tuberculous pleuritis, Sjö gren's syndrome, rheumatoid arthritis, malignant lymphoma, chronic lymphocytic thyroiditis, thyroid lymphomas and Epstein-Barr virus (EBV) infection [3,8]. PEL has been reported to be strongly associated with human herpesvirus-8 (HHV-8) infection and occasionally with EBV infection [4].…”
Section: Discussionmentioning
confidence: 99%
“…The histological subtype in these few cases referred to in the literature was extranodal marginal zone lymphoma [4,5]. The radiological findings of these rare cases were pleural effusion associated with a pleural mass, consolidation or inhomogeneous pleural thickening [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary pleural diffuse large B-cell lymphoma and marginal zone lymphoma have been reported. 28,29 Lymphomatoid granulomatosis is recognized as an angiocentric and angiodestructive disease arising in a variety of extranodal sites. Pathologically it is best classified as an EBV-induced T cell-rich B-cell lymphoma.…”
Section: Othersmentioning
confidence: 99%